2020
DOI: 10.1055/a-1161-0220
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Activity of Artemisia nilagirica Leaves Against Rhipicephalus (Boophilus) annulatus Ticks

Abstract: Since time immemorial, human beings have used various parts of plants in either prevention or treatment of ailments. Plants are rich sources of secondary metabolites such as alkaloids, steroids, terpenoids, flavonoids, and phenolic compounds with a high structural diversity. Many plants/herbs with specific biological activities such as antitumor, antioxidant, anti-inflammatory, antifungal, sedative, and acaricidal activity have been reported. Artemisia nilagirica (C. B. Clarke) Pamp. (Compositae) is a plant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The presence of a high content of sesquiterpenoids and cyclocolorenones in the hexane fraction of A. nilagirica was reported recently [ 45 ]. The presence of elevated content of the terpenoids in A. nilagirica collected from higher altitudes was also reported [ 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The presence of a high content of sesquiterpenoids and cyclocolorenones in the hexane fraction of A. nilagirica was reported recently [ 45 ]. The presence of elevated content of the terpenoids in A. nilagirica collected from higher altitudes was also reported [ 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 93%
“…The acaricidal properties of the plant extracts against R. microplus were attributed mainly to the terpenoids [ 68 , 69 , 70 , 71 ]. Recently, the crude ethanolic extract and the hexane fraction of the ethanolic extract of A. nilagirica were reported with concentration-dependent larvicidal, and adulticidal activities against R. annulatus [ 45 ]. Furthermore, the study also showed the higher effectiveness of the hexane fraction on the inhibition of fecundity over ethanolic extract against R. annulatus ticks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ticks are ectoparasites that transmit many protozoal, viral, and rickettsial diseases that can cause serious harm to animal and human health (Nwanade et al, 2020;Udayan et al, 2020). The high cost, environmental hazards, and development of acaricidal resistance are some of the defects of these chemical acaricides (Udayan et al, 2020) and led to the search for safer and more environmentally friendly alternative methods without compromising efficacy (Nwanade et al, 2020). Plant-based formulations are one of the most promising approaches for controlling ectoparasites (Nwanade et al, 2020;Udayan et al, 2020), including ticks.…”
Section: Discussionmentioning
confidence: 99%